2310. Reasons Pediatric Providers Obtain Endotracheal Aspirate Cultures and How Results Inform Patient Management. (26th November 2018) - Sick-Samuels, Anna; Fackler, Jim; Tamma, Pranita; Milstone, Aaron M
Abstract: Background: Endotracheal aspirate cultures (EACs) are commonly obtained in many PICUs. However, EACs cannot distinguish between bacterial colonization and infection, and may promote antibiotic overuse if collected in patients without clinical signs and symptoms of ventilator-associated infections (VAIs). We examined clinician's reasons to obtain EACs and whether the results informed clinical management. Methods: We conducted a structured survey of nurse practitioners and physicians caring for ventilated children to inform a quality improvement initiative to optimize the use of EACs in the PICU at a tertiary care children's hospital. We assessed EACs obtained from patients mechanically ventilated for at least 24 hours from November 2017 to February 2018. This was a 2-part survey: part 1 conducted within 1–2 days after obtaining an EAC, part 2 conducted after EACs results were reported. Results: 25 surveys were completed. Nearly half (44%) of EACs were obtained for isolated clinical signs of fever, hypotension, laboratory abnormalities, or ventilator increases, while the remainder were obtained for a combination of reasons. Most EACs (60%) were collected as a "pan culture" with urine and blood cultures, and 92% of EACs had a previous EAC. At the time of ordering, providers thought the EAC would help with diagnosis of VAI (68%), antibiotic selection (80%), and believed it was very important for the patient's management (60%). After results were available, 40% of patients were given a diagnosis of VAI. Antibiotic therapy was discontinued in 12% and modified in 16% based on the EAC results. Antibiotics were changed based on a different test in 52%, or unchanged in 20%. Of the patients with a prior EAC, 72% of EACs resulted the same or fewer bacteria. On follow-up, 56% of the providers reported the EAC provided little to no value for the patient's management. Conclusion: A large proportion of EACs were obtained due to isolated changes in a patient's clinical status and most EACs were obtained from patients who had prior EACs. Results were often similar to prior EAC results, infrequently led to changes in antibiotic selection and many providers did not find the results helpful. These findings suggest there is opportunity to standardize and reduce the use of EACs in the PICU. Disclosures: All authors: No reported disclosures.